Karakteristik dan Persepsi Wisatawan terhadap Bauran Pemasaran Kober Mie Setan Jimbaran Kabupaten Badung Bali - Toyo, Maria Fulgensia Railiki; Astina, IB Ketut; Sutaguna, I Nyoman Tri (Jurnal Kepariwisataan dan Hospitalitas; Vol 7 No 1 (2023): Vol.7,No.1,2023, 2023)
The Field of tourism accommodation especially restaurant is a form of business that is very potential and can be developed. In developing a restaurant, of course apply a marketing mix strategy to attract tourist. The value of the success of marketing mix can be measured by the perception of tourist which is this time will be dissscused is Restoran Kober Mie Setan Jimbaran Restaurant. The Purpose of thi research is ti determine how tourist perception about the marketing mix in Restoran Kober Mie Setan Jimbaran Restaurant and to find out the characteristics of tourist visiting Restoran Kober Mie Setan Jimbaran.    In this research using qualitative data and quantitative where the data comes from primary data and secondary data. These data are collected through observation, interviews, quetionnaires, literature study and documentation. Primary data obtained from questionnaires distributed to 100 respondents who were determined by purposive sampling technique and the data analysis technique used the likert scale, validity test and reliability test. Based on the result of the analysis of this research, characteristic can be divided into several group based on gender, province of origin, latest education, occupation, promotion, last income, promotional work, monthly income, length of vacation and based on the number visits and tourist perception about the marketing mix at Restoran Kober Mie Setan Jimbaran Restaurant are in the good category with an average value of 3.97. The indicator with the highest perception value which is a location that is easily accessible by vehicles, gets score 4.20 which is in very good category. The suggestion from the author is to add facilities